KONSELING KELOMPOK TEKNIK SOCIAL MODELLING DALAM MEMINIMALISIR STRES AKADEMIK SISWA SEKOLAH MENENGAH ATAS - Rahmayanti, Meri; Harapan, Edi; Darmawani, Evia (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Student academic stress is influenced by many academic demands that cause students to feel burdened and unable to complete their responsibilities as students because of factors that occur as teenagers and students at school. This study aims to determine the effectiveness of group counseling Social Modeling Techniques in minimizing academic stress in high school students. This study used a quantitative experimental method with pre-test and post-test design. Data collection techniques used observation, questionnaires and documentation with data analysis using the Wilcoxon test to determine changes in students' academic stress behavior before and after being given treatment. It can be concluded that before being given treatment, the pre-test results were obtained with a total score of 269 with an average value of 67.2 in the moderate category. Then post-test group counseling was carried out with a total score of 181 with an average value of 45.2 in the low category. The results of the Wilcoxon test showed a Z count of - 1.826. Becausethe Asymp value. Sig(2-tailed) 0.068 is smaller than 0.5, it can be concluded that the alternative hypothesis (Ha) is accepted and the hypothesis (Ho) is rejected. This means that there is a significant effect after being given group counseling with Social Modeling Technique, which shows that this method is effective in minimizing academic stress of high school students.